2022
DOI: 10.5935/0004-2749.2021-0395
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of the efficacy and safety of Nd:YAG laser vitreolysis for symptomatic vitreous floaters

Abstract: This study aimed to evaluate the long-term safety and efficacy of neodymium-doped yttrium aluminum garnet (Nd:YAG) vitreolysis for symptomatic vitreous floaters as it remains a controversial procedure due to insufficient robust evidence in the literature for the maintenance of the results and absence of adverse effects. Methods: This is an observational extension to the previously presented prospective, randomized, double-blind clinical trial. Eight of thirteen subjects who underwent vitreolysis with YAG laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Shah et al believed that Delaney used a low energy intensity when treating vitreous oaters with the YAG laser, only cutting rather than vaporizing the opacities, which resulted in poor therapeutic effects. A recent long-term follow-up study showed that the therapeutic effect of the YAG laser could be maintained for up to 18 months [7].…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al believed that Delaney used a low energy intensity when treating vitreous oaters with the YAG laser, only cutting rather than vaporizing the opacities, which resulted in poor therapeutic effects. A recent long-term follow-up study showed that the therapeutic effect of the YAG laser could be maintained for up to 18 months [7].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of 3C (computer, consumer electronics, and communication) products and the increase in myopia, 15% of people aged 20–29 years will develop lymphadenopathy, indicating the gradual acceleration of the eye-aging rate. Lymphadenopathy refers to the presence of floating objects in the eye caused by thickened clumps of vitreous jelly [ 2 , 3 , 4 , 5 , 6 , 7 ]. After the age of 40, the vitreous will become dense and gel-like, in which some denser bundles of collagen fibers form.…”
Section: Introductionmentioning
confidence: 99%